PENYELESAIAN SENGKETA TERHADAP INVESTOR ASING JIKA TERJADI SENGKETA HUKUM DALAM PENANAMAN MODAL - Sudiawan, I Nyoman; Ariani, I Gusti Ayu Agung (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 01, Januari 2015)
The paper is titled "Settlement Against Foreign Investors If Happens In Investment Legal Dispute". This paper uses analytical methods and approaches normative juridical legislation. The presence of Act Number 25 of 2007 on Investment, is expected to ensure peace of foreign investors in Indonesia need protection and legal certainty. Foreign investment has a positive impact on the State of Indonesia and the negative impact that needs to be anticipated and a solution found its completion. How resolving disputes between parties investment foreign investment and national parties?As for the purpose of writing is to know how the settlement of investment disputes between foreign investors and the national parties.Investment disputes can be resolved through deliberation, the court. Especially for disputes between foreign investors and the Government of the Republic of Indonesia can be resolved through Arbitration Institute.
Keywords: Dispute Resolution, Foreign Investors